An evidence and consensus based guideline for the management of a child after a seizure. Issue 1 (1st January 2003) - Armon, K; Stephenson, T; MacFaul, R; Hemingway, P; Werneke, U; Smith, S
Abstract : Structured in the format recommended by Hayward et al 1 for guideline reports. Objective: An evidence and consensus based guideline for the management of the child who presents to hospital having had a seizure. It does not deal with the child who is still seizing. The guideline is intended for use by junior doctors, and was developed for this common problem (5% of all paediatric medical attenders) where variation in practice occurs. Options: Assessment, investigations (biochemistry, lumbar puncture, serum anticonvulsant levels, EEG in particular), and/or admission are examined. Outcomes: The guideline aims to direct junior doctors in recognising those children who are at higher risk of serious intracranial pathology including infection, and conversely to recognise those children at low risk who are safe to go home. Evidence: A systematic review of the literature was performed. Articles were identified using the electronic data bases Medline (from 1966 to June 1998), Embase (from 1980 to June 1998) and Cochrane (to June 1998), and selected if they investigated the specified clinical question. Personal reviews were excluded. Selected articles were appraised, graded, and synthesised qualitatively. Statements of recommendation were made. Consensus: An anonymous, postal Delphi consensus development was used. A national panel of 30 medical and nursing staff regularly caring for these children were asked to grade their agreement with the statements generated. They were sent the relevant original publications, the appraisals, and literature review. On the second and third rounds they were asked whether they wished to re-grade their agreement in the light of other panellists' responses. Consensus was defined as 83% of panellists agreeing with the statement. Recommendations in brief: For afebrile seizures all children should have their blood pressure recorded, but no other investigations are routine although a seizing or somnolent child should have blood glucose measured; all children under 1 year should be admitted. For seizures with fever, clinical signs indicating the need to treat as meningitis are given. Children should be admitted if they are under 18 months old, have had a complex seizure, or after pretreatment with antibiotics. Validation: The guideline has undergone implementation and evaluation in a paediatric accident and emergency department, the results of which will be published separately. Only one alteration was made to the guideline as a result of this validation process, which is included here.